Integrating Ecological Literacy into Sundanese Language Learning in Elementary Schools - Susilawati Susilawati; Farid Rizqi Maulana; Nenden Sundari (Lembaga Bale Literasi, 2026)
This study investigates the integration of ecological literacy into Sundanese language learning through a game-based medium, ecological literacy quartet cards, designed for elementary school students. The research responds to the need for contextual, interdisciplinary education that fosters environmental awareness while strengthening language skills, in line with the Kurikulum Merdeka and Sustainable Development Goals (SDGs). The cards embed nine ecological domains (endangered animals, energy sources, types of waste, pollution, green actions, climate change, ecosystems, marine animals, and natural disasters) combined with Sundanese language literacy tasks such as sentence construction, vocabulary enrichment, and role-play. Employing a descriptive quantitative approach, the study involved 32 fifth-grade students in Lebak district, with ecological literacy measured through a 20-item multiple-choice test after the learning intervention. Results showed high achievement across most domains, with mean scores of 90.00 (SD = 6.48), and strongest performance in “Endangered Animals” and “Marine Animals,” indicating the effectiveness of visual narratives and cultural relevance in enhancing retention. Lower performance in “Types of Waste” and “Green Actions” highlights the need for more application-oriented activities to translate knowledge into behavior. The findings demonstrate that integrating ecological and language literacy through simple, low-cost, and culturally embedded game-based media can promote cognitive and affective learning outcomes. This model offers potential scalability for other regional languages and ecological themes, contributing to language preservation and environmental education